PENGARUH PENDEKATAN REALISTIC MATHEMATIC EDUCATION TERHADAP HASIL BELAJAR MATEMATIKA - Khaeriyah, Siti; Sukamto, Sukamto; Untari, Mei Fita Asri (Universitas Slamet Riyadi, 2018)
This study aims to determine the effect of the Realistic Mathematic Education approach on class V mathematics learning outcomes. The type of this research is experimental research in the form of Pre Experimental Design. The population in this study were grade V students of SD Negeri 2 Mororejo, totaling 30 students and fifth grade students of SD Negeri 1 Mororejo, totaling 26 students. The sample in this study were all fifth grade students of SD Negeri 2 Mororejo and all fifth grade students of SD Negeri 1 Mororejo. Data in this study were obtained through tests, observations and interviews. Based on the results of the analysis after getting treatment shows that the learning outcomes of mathematics increased by using the Realistic Mathematic Education approach. The data obtained from the average value of the pretest of the experimental class was 65.16 and the average posttest score increased to 80.66. Calculation of simple linear regression test obtained Fcount value of 2776 and Ftable value of 4.20, because Fcount> Ftable is 2776> 4.20 then H0 is rejected and Ha is accepted.